EPILEPSY IN PATIENTS WITH SUPRATENTORIAL MENINGIOMAS - Bogdanovic, Ivan; Grujičić, Danica; Ristić, Aleksandar (Medicinski podmladak, 2023)
Meningiomas are the most common primary intracranial tumors. They are mostly slow-growing and of benign histopathology rendering them curable by surgery alone. Symptomatic lesions depend on the location with signs of focal neurological deficits or increased intracranial pressure. Seizures are the presenting symptoms in approximately 30% of supratentorial meningiomas. Epileptogenesis in these patients is not yet clearly defined. Epilepsy negatively affects the quality of life, limits independence, and impairs cognition, as well as increases the risk for psychiatric comorbidities including depression. Although surgical resection may offer seizure freedom in more than 60% of meningiomas, seizures persist after surgical resection in a significant number of patients. The potential preoperative and postoperative predictors for seizures in meningioma patients have been analyzed in multiple studies. Anti-seizure medications are employed in the treatment of these patients, however, their application is often followed by adverse neurocognitive side effects and inefﬁcacy in some patients. Understanding various clinical, histopathological, and surgical factors potentially associated with epilepsy can help guide more effective seizure control and allow for better assessment of risk before and after surgery. Patients with persistent seizures may benefit from referral to an epilepsy center for evaluation.
Keywords: epilepsy, meningioma, tumor, predictors, surgery